Ownership Structure and Debt Financing Decision of Vietnamese Listed Companies - Thai, Nguyen Hoang; Son, Nguyen Hoang Thien (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Raising capital not only helps firms to meets the capital needs for production and business's development, but also supports them to endure financial risks. Hence, the problem of proactively choosing a reasonable financing structure between equity and debt to maximize corporate value becomes more and more imperative. This paper aims to investigate the relationship between corporate governance, especially ownership structure, and funding decision of Vietnamese listed firms. The study data include 209 non-financial companies with 1,045 firm-year observations obtained from two main stock exchange in Vietnam, including Hanoi Stock Exchange and Ho Chi Minh Stock Exchange, covering a 5-year period from 2014 to 2018. The finding of this study reveals that CEOs, state government, and foreign ownership significantly impact on capital structure, whilst there is no evidence to support the correlation between board ownership and funding decision. As for capital structure specific control variables, including firm size (Size), current ratio (CAR), cash ratio (OPCFTA), tangibility ratio (PPETA), and profitability (ROA) significantly effect on firm leverage.